Laser welding a practical guide - Dawes, Christopher (Woodhead Publishing series in welding and other joining technologies, 1992)
Enables the reader both to understand and to use, in a practical manner, laser welding. The author explains the principles of laser welding and provides examples of industrial applications, examines many aspects of laser welding and devotes a complete chapter to safety